Frictional strength of ground dolerite gouge at a wide range of slip rates. Issue 4 (8th April 2016) - Wada, Jun‐ichi; Kanagawa, Kyuichi; Kitajima, Hiroko; Takahashi, Miki; Inoue, Atsuyuki; Hirose, Takehiro; Ando, Jun‐ichi; Noda, Hiroyuki
Abstract: We conducted a series of rotary‐shear friction experiments on ground dolerite gouges, in which the amount of adsorbed moisture increases with grinding time ( t gr ), at room temperature and humidity, a normal stress of 2 MPa, and constant equivalent slip rates ( V eq s) ranging from 20 µm/s to 1.3 m/s. Their frictional strength changed with V eq and t gr in three different ways depending on V eq and the gouge temperature ( T ). At V eq ≤ 1.3 cm/s, T did not exceed 80°C, and the steady state friction coefficient ( μ ss ) ranged from 0.59 to 0.80. μ ss changes little with V eq, while μ ss at a given V eq systematically increases with t gr probably due to moisture‐adsorbed strengthening of gouges. At V eq = 4 cm/s, T exceeded 100°C, and dehydration of gouges resulted in roughly the same μ ss values (0.60–0.66) among gouges with different periods of t gr . At V eq ≥ 13 cm/s, T reached 160–500°C, and μ ss dramatically decreases with V eq to 0.08–0.26 at V eq = 1.3 m/s, while μ ss at a given V eq systematically decreases with t gr . At these fast V eq s, dehydration of gouges likely occurred too fast for water vapor to completely escape out from the gouge layer. Therefore, faster dehydration at faster V eq possibly resulted in a larger pore pressure increase and lower frictional strength. In addition, because gouges with longer periods of t gr contain larger amounts of adsorbed moisture, they became weaker due to larger increases in pore pressure and hence larger amounts of reduction in frictional strength. Key Points: Moisture adsorbed in ground dolerite increases with grinding time Moisture strongly affects frictional strength of ground dolerite